Fractal analysis of electrical tree grown in silicone rubber nanocomposites - Z. Nawawi; M. A. B. Sidik; M. I. Jambak; R. F. Kurnia; C. L. G. Pavan Kumar; M. H. Ahmad; Z. Buntat (Universitas Ahmad Dahlan, 2020)
Electrical treeing is one of the main reasons for long-term degradation of high voltage insulation especially in the cable accessory which commonly made from silicone rubber due to non-uniformly structures of the cable accessories. Recently, the combination of nanofillers with the silicone rubber matrix can reduce the possibility of the electrical treeing to grow further by changing its patterns and slow-down its propagation. However, the influences of nanofillers on the tree hindrance and its patterns are not well understood. This paper explores the influence of nanofiller on tree pattern in silicon rubber. The electrical tree patterns were characterized using fractal analysis. The box-counting method was used to measure the fractal dimension and lacunarity to obtain the structure of the tree pattern during the electrical tree growth. The structure of the electrical tree in silicone rubber nanocomposites has higher fractal dimension and lacunarity. Sample with nanofiller possesses dominant fractal dimension of tree growth compared to the sample without nanofiller.